PERSEPSI WISATAWAN MUSLIM TERHADAP SARANA PENUNJANG WISATA HALAL DIKAWASAN DESA SEMBALUN LAWANG LOMBOK TIMUR - Sri Wahyulina; Sri Darwini; Weni Retnowati; Sri Oktaryani (Master of Management, Mataram University, 2018)
The purpose of this research was to explore the perception of Muslim Travelers toward Halal Tourism supporting facilities on the Sembalun Lawang village. The research method that used in this research was descriptive method. This research shown the Toilet, Trash and places of worship are becoming the most important means of desired by the tourists who visit the Sembalun regions.The researcher found the condition of the Hotel or other accommodation danTempat Worship is there in halal tourism Sembalun regions, East Lombok Regency is very good compared with the condition of the other supporting facilities. The travelers feel facilities that easy to reach within in the Sembalun Lawang are worship place, the Hotel/accommodation/Lodging, restaurant/dining and two wheeled vehicle parking Area. The results of this research suggest to Government and societies of Sembalun Lawang immediately provide toilets and Trash at every attraction in the Sembalun Lawang. The Government should immediately set up hotels and other akodomasi so that sufficient for the number of tourists coming to the Sembalun Lawang and not to interfere with the natural landscape Sembalun regions as the main attraction of this area. Faslilitas parking for tour buses should be immediately provided. For the banking and Government should cooperate in facilitating ATM for tourists to take the cash.Keywords: Perception, Travellers, Muslims, A Means Of Supporting Tourism, Halal, Sembalun Regions Mace